Placing a crown on Dy-III - a dual property Ln(III) crown ether complex displaying optical properties and SMM behaviour - Gavey, Emma L.
Two mononuclear Dy-III crown ether complexes [Dy(15C5)(H2O)(4)](ClO4)(3)center dot(15C5)center dot H2O (1) and [Dy(12C4)(H2O)(5)](ClO4)(3)center dot H2O (2) have been prepared and characterized. X-ray diffraction studies show that both compounds crystallize as half sandwich type structures with muffin and pseudo-capped square antiprismatic geometries respectively. Despite the comparable local environments of the Dy-III ions they display remarkably different dynamic magnetic properties with only 1 displaying SMM properties in zero field. The solid state emission spectra for both 1 and 2 display sharp bands associated with f-f transitions. From the fine structure of the F-4(9/2) -> H-6(15/2) band, the Stark splitting of the H-6(15/2) ground state permitted the energy difference between the ground and first excited state to be determined. For 1 this value (Delta E = 58.0 +/- 3.0 cm(-1) ) is in excellent agreement with ab initio calculations and the experimentally observed SMM behaviour. For 2, the photoluminescence data and theoretical calculations support a less well isolated ground state (Delta E = 30 +/- 3.0 cm(-1)) in which a rapid relaxation process affords no SMM behaviour in zero-field.